ANALISIS FAKTOR PENENTU KINERJA EKSPOR MANUFAKTUR: SUATU STUDI DI TIGA NEGARA BERKEMBANG - Saputra, Putu Mahardika A. (Journal of Indonesian Economy and Business, 2006)
The objective of this research is to analyze the influence of some determinant variables,such as external market conditions (world demand), the competitiveness, exportdiversification and the level of technology on three developing countriesâ exportperformance. Each country was analyzed in both terms, as an individual country and acountry group. The analysis will take period during 1997-2001. This research examinesalso the differences among three countries in the light of changes in both externaldemand and domestic supply factors over the period by using sector-level data. Theresults show that export performance in most countries is relatively more sensitive todomestic factors, particularly the ability to compete in world markets (competitiveness)than to other factors. This research support also the emphasis placed by the opponents oftrade pessimism on the importance of policies designed to improve domestic supplycondition for exportables.Keywords: export, export promotion strategy, import substitution strategy, externalÂ demand and domestic supply factors.